Philometroides acanthopagri sp. nov., a new philometrid (Nematoda, Philometridae) from the musculature of Acanthopagrus latus (Sparidae) from marine waters of Iraq - Moravec, František; Jassim, Abdul Amer R; Al-Salim, Nadrah K (Acta parasitologica, 2012)
A new nematode species, Philometroides acanthopagri sp. nov. (Philometridae), is described from gravid and subgravid specimens found in the musculature near pectoral fins and in nasal cavity of the yellowfin seabream Acanthopagrus latus (Houttuyn) (Sparidae, Perciformes) from marine waters off the coast of southern Iraq. Based on light and scanning electron microscopical examination, the new species differs from its congeners in a combination of morphological and biometrical features. It is the first species of Philometroides reported from a sparid fish and the first representative of this genus recorded from fishes in the Arabian Gulf. A key to Philometroides species parasitizing marine and brackish-water fishes is provided.
Keywords: mikroskopie; Dracunculoidea; nematodózy; biometrie; Microscopy; Irák; Perciformes; nosní dutina; Muscles; ploutve zvířat; Seawater; Iraq; Nematode Infections; Animal Fins; mořská voda; svaly; Biometry; Nasal Cavity; zvířata; nemoci ryb; Animals; Fish Diseases